Dynamics of urinary KIM-1 as a biomarker of acute kidney injury in cancer patients undergoing cisplatin-based chemotherapy - N. S. Sergeeva; T. A. Karmakova; V. V. Savchina; T. I. Deshkina; E. Yu. Karpenko; L. V. Bolotina; I. I. Alentov; N. V. Marshutina; A. A. Fedenko (Сибирский онкологический журнал, 2023)
Platinum is the main component of the most chemotherapy (CT) regimens, but their use may be limited because of nephrotoxicity. Kidney injury molecule 1 (KIM-1) is considered as an early marker of cisplatininduced acute kidney injury (AKI). The aim of our study was to evaluate the changes in the burinary levels of KIM-1 (uKIM-1) in cancer patients receiving nephrotoxic CT throughout the entire course of the treatment. Material and Methods. The level of uKIM-1 was determined by enzyme immunoassay in untreated 19 patients with solid malignancies before each CT cycle (regimens with cisplatin or oxaliplatin) and every next day after cytostatic drugs administration. uKIM-1 values were normalized to urinary creatinine concentration (uKIM-1). The kidneys function was assessed by the serum creatinine (sCr) and glomerular fltration rate (GFR) value. Results. According to laboratory parameters, renal function in patients before treatment corresponded to normal ranges. During CT, an increase in sCr by more than 50 % (decrease in GFR to 68 ml/min/1.73 m2 ), which corresponded to stage I AKI (KDIGO) was revealed in one patient (5.3 %) only. uKIM-1 levels before CT were above the upper limit of normal range (3.4 ng/mguCr) in 3 patients (15.8 %; median 2.1 ng/mguCr); at the beginning of the 2nd cycle of CT they were increased in 9 patients (47.4 %; median 3.2 ng/mguCr; p=0.0025, Mann-Whitney test); at the beginning of the 3rd cycle of CT uKIM-1 levels were increased in 12 patients (63.2 %; median 4.9 ng/mguCr; p=0.00007). During CT with cisplatin the average level of uKIM-1 increased with each subsequent cycle, in most cases it increased already the day after the administration of cytostatic drugs. No increase in uKIM-1 levels was observed during treatment with oxaliplatin-based regimens. The achievement of the threshold uKIM-1 level of 6.0 ng/mguCr at the beginning of the next cycle of CT was signifcantly associated with a high risk of its further increase (RR=18.8; p=0.0051). Conclusion. An increase in the level of uKIM-1 after cisplatin administration can be regarded as a marker of subclinical kidney damage. In the future, the increase in uKIM-1 level at the beginning of the cycle of CT may be a reason for enhanced preventive measures or the appointment of less nephrotoxic treatment regimens.